The Genus Coelocrania and the Resurrection of the Genus Pseudosastra (Coleoptera: Chrysomelidae: Galerucinae) - Mohamed S. Mohamedsaid (Psyche: A Journal of Entomology)
The genus Coelocrania Jacoby is reviewed, with the resurrection of the genus Pseudosastra Jacoby. Four new species are herein described from Malaysia: Pseudosastra depressa, P. ghazallyi , P. indah, and P. latiffi. Keys to the species of Coelocrania and Pseudosastra are provided.